Cutaneous Silicone Granuloma Mimicking Breast Cancer after Ruptured Breast Implant - El-Charnoubi, Waseem Asim Ghulam (Hindawi Publishing Corporation, 2011)
Cutaneous manifestations due to migration of silicone from ruptured implants are rare. Migrated silicone with cutaneous involvement has been found in the chest wall, abdominal wall, and lower extremities. We describe a case of cutaneous silicone granuloma in the breast exhibiting unusual growth mimicking breast cancer after a ruptured implant.